Family and household structure are associated with acute type 1 diabetes complications: results of cross‐sectional analyses. Issue 12 (26th January 2020) - Baechle, C.; Stahl‐Pehe, A.; Castillo, K.; Gontscharuk, V.; Holl, R. W.; Rosenbauer, J.
Abstract: Aim: To examine the association of family/household structure with short‐term diabetes complications in adolescents and emerging adults with early‐onset type 1 diabetes in more detail. Methods: Data on 1690 11–21‐year‐olds with type 1 diabetes were used to estimate associations of family/household structure with self‐reported severe hypoglycaemia, hospitalizations for severe hypoglycaemia or diabetic ketoacidosis, applying multiple negative binomial regression. Results: Compared with living with both biological parents living with a single mother was associated with an increased rate of hospitalizations for ketoacidosis (incidence rate ratio 1.71, 95% CI 1.00–2.82). Incidence rate ratio of hospitalizations for ketoacidosis was similar (1.67, 95% CI 0.91–3.07) if the mother lived with a partner, however, hypoglycaemia‐related hospitalizations increased (3.66, 95% CI 1.54–8.71). Participants living with a single father had 4.43 (95% CI 1.30–15.05) /10.42 (95% CI 1.55–70.22) times higher rates of severe hypoglycaemia and related hospitalizations, while living with a father and his partner was associated with an increased incidence rate ratio of hospitalizations for ketoacidosis (3.48, 95% CI 0.96–12.63) compared with living with both biological parents. Conclusions: Findings of our exploratory analyses point to different self‐reported diabetes outcomes depending on the family/household structure. If confirmed in future studies, they may help to identify young people with diabetes at risk of short‐term diabetes complications. What's new?: In this exploratory study, for the first time, associations of family structure with short‐term diabetes‐related complications are analysed in detail. Living with a single parent with or without a partner is differently associated with short‐term diabetes outcomes. Differences existed despite adjustment for differences in socio‐economic status. If confirmed in future studies, our findings may help to identify young people at risk of short‐term diabetes complications.